2018
DOI: 10.1038/s41467-017-02758-9
|View full text |Cite
|
Sign up to set email alerts
|

Radionuclides transform chemotherapeutics into phototherapeutics for precise treatment of disseminated cancer

Abstract: Most cancer patients succumb to disseminated disease because conventional systemic therapies lack spatiotemporal control of their toxic effects in vivo, particularly in a complicated milieu such as bone marrow where progenitor stem cells reside. Here, we demonstrate the treatment of disseminated cancer by photoactivatable drugs using radiopharmaceuticals. An orthogonal-targeting strategy and a contact-facilitated nanomicelle technology enabled highly selective delivery and co-localization of titanocene and rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
64
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(69 citation statements)
references
References 37 publications
2
64
1
2
Order By: Relevance
“…To date, many fluorescence imaging agents have been designed for tumor imaging and/or therapy, such as radionuclide, iron nanoparticles, and near-infrared (NIR) agents (Kotagiri et al, 2018;Lu et al, 2018). Among all the imaging agents, indocyanine green (ICG) is the only NIR agent approved for clinical use by Food and Drug Administration (FDA) (Hwang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…To date, many fluorescence imaging agents have been designed for tumor imaging and/or therapy, such as radionuclide, iron nanoparticles, and near-infrared (NIR) agents (Kotagiri et al, 2018;Lu et al, 2018). Among all the imaging agents, indocyanine green (ICG) is the only NIR agent approved for clinical use by Food and Drug Administration (FDA) (Hwang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Cherenkov radiation occurs when a particle travels faster than the speed of light through a medium, which is seen with multiple radioisotopes (Shaffer, Pratt, & Grimm, ) (Hoogendam et al, ; Phillips et al, ; Pratt, Shaffer, & Grimm, ). Research shows that Cherenkov radiation from medical radioisotopes can activate photosensitizer to produce ROS (Kotagiri et al, ). Both external‐beam radiation and internal irradiation are widely utilized for cancer treatment, underscoring the clinical relevance and prospects of X‐PDT and CR‐PDT.…”
Section: Introductionmentioning
confidence: 99%
“…[38,46] CD146-targeted RIT will hopefully lead to tumor-specific lethal DNA damage and enhanced immune responses. Although studies have shown that Cerenkov radiation from beta emitters (such as 64 Cu and 18 F) can be used to excite photosensitizers (such as TiO 2 nanoparticles) to realize deep-tissue PDT, [48,49] future studies are needed Adv. Although studies have shown that Cerenkov radiation from beta emitters (such as 64 Cu and 18 F) can be used to excite photosensitizers (such as TiO 2 nanoparticles) to realize deep-tissue PDT, [48,49] future studies are needed Adv.…”
Section: Discussionmentioning
confidence: 99%